Inhibition of triple-negative breast cancer growth via delphinidin-mediated suppression of the JAK2/STAT3/PD-L1 pathway - Xiaoping Yu; Xiaolong Song; Jiali Yan; Ziting Xiong; Lujie Zheng; Yan Luo; Fengcheng Deng; Yanfeng Zhu (Food & Nutrition Research)
Background: Breast cancer is a leading cause of cancer-related mortality among women globally, with triple-negative breast cancer (TNBC) being particularly aggressive. Delphinidin (Dp), an anthocyanin monomer, has shown promising health benefits. Objective: This study investigates the effects of Dp on TNBC and aims to elucidate its specific mechanisms of action. Design: We utilized cell counting kit-8 (CCK-8) assays, colony formation assays, and scratch assays to evaluate the influence of Dp on the proliferation and migration of TNBC cells. Flow cytometry was employed to analyze programmed cell death-ligand 1 (PD-L1) and Cluster of Differentiation 69 expression, while Western blotting assessed the levels of PD-L1, Janus Kinase 2 (JAK2), Signal Transducer and Activator of Transcription 3 (STAT3), p-JAK2, p-STAT3, and exosomal marker proteins. Additionally, enzyme-linked immunosorbent assay (ELISA) was conducted to measure concentrations of PD-L1, interferon-γ (IFN-γ), and tumor necrosis factor-β (TNF-β). Results: Dp effectively inhibited TNBC cell proliferation and migration, as evidenced by CCK-8, colony formation, and scratch assays. Flow cytometry and Western blot analysis indicated a reduction in PD-L1 expression in TNBC cells. Meanwhile, we successfully isolated TNBC cell-derived exosomes, with ELISA experiments showing a decrease in PD-L1 expression in these exosomes following Dp treatment. In a co-culture system with TNBC and Jurkat cells, Dp enhanced Cluster of Differentiation 69 expression and reactivated Jurkat cells, resulting in increased secretion of IFN-γ and TNF-β. Additionally, Dp significantly reduced the p-JAK2/JAK2 and p-STAT3/STAT3 ratios in TNBC cells. Conclusion: Dp may exert its anti-TNBC effects by downregulating PD-L1 expression in TNBC cells and exosomes through the JAK2/STAT3 signaling pathway, potentially restoring T cell activity and modifying the tumor microenvironment.